Intelligent Virtual Agents 13th International Conference, IVA 2013, Edinburgh, UK, August 29-31, 2013. Proceedings - Aylett, Ruth.; Krenn, Brigitte; Pelachaud, Catherine; Shimodaira, Hiroshi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the proceedings of the 13th International Conference on Intelligent Virtual Agents, IVA 2013, held in Edinburgh, UK, in August 2013. There was a total of 94 submissions. The 18 full and 18 short papers presented in this volume were carefully reviewed and selected for inclusion in the book. In addition, the volume lists the 34 posters which were on display during the conference. The papers are organized in topical sections named: cognitive models; applications; dialogue, language, speech; non-verbal behaviour; and social, cultural models and agents.
Cognitive Models -- Applications -- Dialogue, Language, and Speech -- Non-verbal Behaviour -- Social, Cultural Models and Agents -- Tools and Techniques.
Keywords: Computer science; Artificial intelligence; Computer simulation; Computer Science; Artificial Intelligence (incl. Robotics).; User Interfaces and Human Computer Interaction; Simulation and Modeling